Sensitivity analysis of a Venturi shaped structure for cross-flow turbines. Issue 1 (31st December 2022) - Gabl, Roman; Burchell, Joseph; Hill, Mark; Ingram, David M.
Abstract : Tidal energy is one of the world's most predicable renewable energy sources and therefore holds great potential to be a valuable building block for the decarbonisation of electricity production. This paper focuses on a Venturi shaped duct structure (shroud) to accelerate the flow speed at a vertical axis tidal turbine utilising the low static pressure created at the exit of the shroud. This concept is known as a Davidson Hill Venturi (DHV) turbine. By constructing the nozzle and diffusor using hydrofoils, initial demonstrations indicate increased system efficiency. However, owing to the potential number of geometric and structural hydrofoil variations, only a general description of the location of the hydrofoils is provided in order to facilitate modelling while allowing for future geometric variations to be devised. The conducted investigations focus on the influence of the nozzle and diffusor sections as the main geometry variations, identifying the length component in the orthogonal direction as the dominant parameter. By modelling multiple combinations of these variables it is clear that higher fluid velocities result in larger forces which must be supported by the devices structure. Small adjustments to the reference geometries hydrofoil placement and spacing provided improvements to the fluid flow. Thus, taking the slight alteration to the geometry as this papers main outcome, a further in a 3D-simulation study, including turbine interaction and rotation, is to be completed to fully characterise the systems benefits. The insights gained from this work will allow a reduction in computational costs for the detailed optimisation and study into the adaption of the concept for a wide range of (environmental) boundary conditions.